Language attitudes, identity and L1 maintenance: A qualitative study of Vietnamese ethnic minority students. (October 2016) - Nguyen, Trang Thi Thuy; Hamid, M. Obaidul
Abstract: This article examines a group of Vietnamese ethnic minority students' language attitudes in relation to their identity and minority language (L1) maintenance by focusing on three languages—their L1, Vietnamese and English—in terms of integrative/instrumental orientations and ideal/ought-to language selves. Multiple semi-structured interviews with eight college-age minority students were the main source of the data. The students were found to have displayed the integrative orientation in valuing their L1, and the instrumental orientation in valuing Vietnamese and English. However, the integrative and instrumental orientations appeared to be ambiguous, which may not contribute to a comprehensive understanding of their language attitudes. A combination of integrative and instrumental orientations and ideal and ought-to language selves appeared more relevant to understand the students' language attitudes and identity. As the students' attitudes were influenced, to a large extent, by the utility of languages, it is argued that positive attitudes alone are not enough to ensure L1 maintenance or identity empowerment. Institutional support is necessary to promote the use of minority languages for their maintenance.